Turbinoplasty of concha bullosa: a useful adjunct in improving nasal airway - Venkataramani, Nithya; Sachidananda, Ravi; Vasista, Srividya Rao (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Concha bullosa is the pneumatisation of middle turbinate which causes crowding and obstruction of the middle meatus. This is associated with contralateral septal deviation. The objective of this study is to evaluate, if a concha bullosa turbinoplasty has any added value in improving nasal symptoms when performed as adjunct with septoplasty. Methods: Retrospective analysis of the hospital database was done and details of patients who underwent septoplasty along with concha bullosa turbinoplasty was collected and the patients were telephonically contacted to record their symptom improvement. Results: Details of nineteen patients who underwent concha bullosa turbinoplasty with septoplasty were studied, mean age of the patients was 31.26 years and the mean follow up period was 22 months. All patients had improvement in symptoms with most completely asymptomatic, the others had mild to moderate symptoms. Conclusions: Concha bullosa turbinoplasty as an adjunct to septoplasty does alleviate the symptom of nasal obstruction.